Efektivitas Program Pengembangan Kompetensi Guru dalam Meningkatkan Kinerja di Sekolah - Siti Syevila; Denny Fitriani; Tengku Darmansah; Faradillah Amelia; Zoe Zarka Syafiq (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
The existence of a teacher competency development program is very important to improve their performance so that they can be said to be professional teachers. The teacher competency development program functions as a teacher transformation process. The real world of teacher work is student learning in classroom learning activities. Teacher performance is all the results of the teacher's efforts in delivering the learning process. educational goals, which include all activities related to his duties as a teacher. This study aims to explore the effectiveness of teacher competency development programs in improving performance in schools. The research was conducted using the literature study method, which involves collecting data to understand and study theories from various relevant literatures. Teacher competency development is becoming increasingly important and necessary, especially in the context of improving career paths in functional teacher positions. Without continuous self-development, a teacher will encounter difficulties, even difficult to achieve a higher functional position. Performance evaluation is a systematic process for determining the specific benefits or job measures of an organization in the task of establishing internal comparability.